Border following–based reversible watermarking algorithm for images with resistance to histogram overflowing. (May 2020) - Tang, Xin; Zhou, Linna; Liu, Dan; Shan, Weijie; Zhang, Yi
Histogram shifting is an effective manner to achieve reversible watermarking, which works by shifting pixels between the peak point and its nearest zero point in histogram to make room for watermark embedding. However, once zero point is absent, the algorithm suffers from overflowing problem. Even though some works attempt to deal with this risk by introducing auxiliary information, such as a location map, they occupy a lot of embedding capacity inevitably. In this article, in order to deal with overflowing problem efficiently, we propose a border following–based reversible watermarking algorithm for images. With the help of border following algorithm and pre-processing, available regions with at least one zero point are recognized to embed watermark so that auxiliary information is not needed any more. And the algorithm utilized also ensures the same border can be re-recognized from the watermarked image without error, thus the correctness is also guaranteed. The performance of the proposed algorithm is evaluated using classic image datasets in this area, and the results not only validate the effectiveness of the proposed algorithm but also indicate its advantages compared with the classic histogram shifting–based reversible watermarking algorithm as well as the state of the art.